Peran Guru Pendidikan Agama Islam Dalam Menanggulangi Kenakalan Siswa - Rinah, Rinah (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
This research is motivated by the existence of juvenile delinquency which refers to behavior in the form of deviations or violations of applicable rules or norms, be it social, religious, or legal norms. The objective of this research is to the role of Islamic religious education teachers in tackling student delinquency. The research subjects were teachers of SMP N 8 Pekanbaru. Research method in this study, the researcher used a qualitative descriptive approach, which is a research procedure based on descriptive data. Theresults of this study PAI teachers convey knowledge and shape the personality and morals of students. Apart from acting as a teacher and parent of students at school, the teacher also motivates students through religious activities held at school, such as Islamic holiday celebrations, Annisa forum, Arijjal forum, BTQ, Hafiz Qur'an, and Muhadarah. Factors driving students to misbehave are the influence ofpeers who invite them to deviate, an unhealthy social environment, and no support from parents and teachers who often scold students in public.